2014
DOI: 10.1016/j.biomaterials.2013.12.053
|View full text |Cite
|
Sign up to set email alerts
|

Application of stem cells derived from the periodontal ligament or gingival tissue sources for tendon tissue regeneration

Abstract: Tendon injuries are often associated with significant dysfunction and disability due to tendinous tissue’s very limited self-repair capacity and propensity for scar formation. Dental-derived mesenchymal stem cells (MSCs) in combination with appropriate scaffold material present an alternative therapeutic option for tendon repair/regeneration that may be advantageous compared to other current treatment modalities. The MSC delivery vehicle is the principal determinant for successful implementation of MSC-mediate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
91
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(95 citation statements)
references
References 46 publications
4
91
0
Order By: Relevance
“…A wide range of donor cell types have been used to promote tendon healing in pre-clinical studies, including bone marrow-derived mesenchymal stem cells (BMSCs) [3,4,5], periodontal ligament or gingival tissue [6], dermal fibroblast [7], tenocytes [8], peripheral blood-derived MSCs [9,10] and embryonic stem cell derived MSCs (ESC-MSCs) [11]. Each cell source has its limitations including inferior proliferation, differentiation and collagen production abilities of tenocytes [12,13,14,15], risk of teratoma formation of ESCs as well as risk of ectopic bone [3] and tumor induction [16] of BMSCs when using a certain scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of donor cell types have been used to promote tendon healing in pre-clinical studies, including bone marrow-derived mesenchymal stem cells (BMSCs) [3,4,5], periodontal ligament or gingival tissue [6], dermal fibroblast [7], tenocytes [8], peripheral blood-derived MSCs [9,10] and embryonic stem cell derived MSCs (ESC-MSCs) [11]. Each cell source has its limitations including inferior proliferation, differentiation and collagen production abilities of tenocytes [12,13,14,15], risk of teratoma formation of ESCs as well as risk of ectopic bone [3] and tumor induction [16] of BMSCs when using a certain scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…However, little is known about which cell type acts as the origin of dental stem cells and how they differentiate into functional cells. Certain dental stem cells [periodontal ligament stem cells (PDLSCs) and stem cells from apical papilla (SCAPs)] have been verified to have variable differentiation potentials and thus can be used in oral tissue engineering (Sumita et al, 2006;Moshaverinia et al, 2014). The osteoblastic differentiation abilities of PDLSCs and SCAPs have been confirmed and their functions in promoting osteogenesis have also been verified in multiple studies (Cate, 1996;Yang et al, 2009).…”
Section: Introductionmentioning
confidence: 88%
“…To our knowledge, periodontal ligament cells are principal functional cells, regenerating and reconstructing the periodontal tissues (Moshaverinia et al, 2014). The periodontal ligament is a source of pluri-potent cells and molecular factors that control cellular events in the periodontal tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The reported sources of mesenchymal stem cells include bone marrow (Skvortsova et al 2008), adipose tissue (Gutierrez-Fernandez et al 2013a), embryo (Liu et al 2009), placenta (Kranz et al 2010), dental pulp and periodontal ligament (Moshaverinia et al 2014;Vasandan et al 2014). Other sources, including palatine tonsil (Janjanin et al, 2008), dermis (Feisst et al 2014), and skeletomuscular system (Aydin et al 2014;Mason et al 2014), have also been reported.…”
Section: Advantages Of Therapeutic Use Of Adipose-derived Mesenchymalmentioning
confidence: 96%